Effect of heating on the molecular carbon structure and the evolution of mechanical properties of briquette coal. (15th December 2021) - Gan, Qingqing; Xu, Jiang; Peng, Shoujian; Yan, Fazhi; Wang, Ruifang; Cai, Guoliang
Abstract: Preparing briquette coal (BC) via the heating and pressure method can improve its low mechanical strength in physical simulation tests and gas outbursts while increasing experimental reliability. However, the influence of temperature on the mechanical properties of BC, microstructure, and the reasons underlying the evolution of mechanical strength of BC analyzed in terms of the carbon molecular structure of coal still need to be further studied. For this purpose, a rock mechanics test system, scanning electron microscopy, X-ray diffraction, and Fourier Transform Infrared Spectroscopy were used to analyze the optimum temperature for BC preparation and identify how the heating temperature affects the molecular carbon structure of BC to increase its strength. The result showed that as the temperature increases from 150 °C to 600 °C, the aromatic d002 layer spacing decreased, whereas the aromatic layers of La and Lc increased, leading to an order degree increase of coal molecules. In addition, Hal /H and CH2 /CH3 decreased, whereas Aar /Aal increased, indicating that the aliphatic chains shortened and the aromaticity increased, ultimately improving the strength of BC. However, when the temperature exceeds 300 °C, the pores suffers damage, increasing the width of the pores and crack. Through uniaxial compression, the mechanical strength of BC first increases and then decreases. Moreover, the mechanical strength, Poisson's ratio, and elastic modulus at 300 °C were close to that of raw coal (RC). These results provide guidance to prepare excellent raw materials needed for large-scale physical simulation experiments to prevent and control coal and gas outbursts. Highlights: Making accurate coal samples would aid prevention of coal mine gas disasters. The mechanical strength at 300 °C was close to raw coal. The order degree of coal carbon molecule increased as temperature increased. The aromaticity of coal carbon molecule as temperature increased.